Pengaruh Pengaruh Investasi terhadap Pertumbuhan Ekonomi Regional di Indonesia: Institut Pertanian Bogor - Tri Handayani Murti; Sahara . (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2019)
Investment is one of the driving factors for economy. Investment form are Foreign Direct Investment (FDI) and Domestic Investment (DI). The Jokowi-JK government launched 16 economic policy packages that is expected to increase investment both Foreign Direct Investment (FDI) and Domestic Investment (DI) for each region in Indonesia. This study aims to analyze the factors that influence investment both PMA and PMDN as well as the influence of PMA and PMDN on regional economic growth in Indonesia. This study uses data of panel data of 34 provinces in Indonesia during 2015-2018. The method used in this research to descriptive and quantitative analysis in the form of panel data using the Fixed Effect Model (FEM). The results show that economic growth, the rate of economic growth, export-import and the workforce were proven to influence foreign direct investment and domestic investment. In addition, FDI, domestic investment, labor force and exports have a positive and significant effect on economic growth while imports have a negative but not significant effect. The government needs to to minimize imbalances in economic growth, export-import, labor force and stabilize the rate of economic growth to increase FDI and domestic investment in each region in Indonesia. FDI and DI are expected to be directed to the potential sectors of each region in Indonesia.